OUTCOME OF PATIENT SAFETY CULTURE USING THE HOSPITAL SURVEY ON PATIENT SAFETY CULTURE (HSOPSC) IN ASIA: A SYSTEMATIC REVIEW WITH META ANALYSIS - Rizky Anggraita Damayanti; Adang Bachtiar (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Patient safety is a critical component of the quality of health care. In the process, it allows health services, especially hospitals, to well understanding aspects of patient safety. Hospital Survey on Patient Safety Culture (HSOPSC) was established to examines patient safety culture and the correlation between patient safety culture composite hospitals in Asia. This study aims to assess patient safety culture which using Hospital Survey on Patient Safety Culture (HSOPSC). Methods: Systematic Review and meta-analysis method by using PRISMA-P 2015 were used in this study. We were collected through searching electronic literature from Elsevier, Science Direct, PubMed, and Google Scholar by using keywords "Hospitals Survey on Patient Safety Culture" and"HSOPSC Asia" published from January 2009 to January 2019. English language papers only are used as the inclusion criteria. Results: Totally,160 articles were found and after deleting duplicates document, 126 journals left. Finally, 16 eligible journals which fulfil the inclusion criteria were reviewed. The HSOPSC overall average percentage positive response rate for HSOPSC was 53.58. Of the 12 patient safety composites evaluated, the highest average score is teamwork within unit 74.29±11.92. The bivariate analysis used Spearman correlation for correlation between patient safety composite, the composite Frequency of Event Reported the weakest correlation with teamwork within unit ( r = 0.052), and the composite teamwork across unit had the strongest correlation with teamwork within unit (r = 0.761). Conclusion: Patient safety culture is crucial toward improving overall performance and quality of services in hospitals, especially teamwork within unit. Culture safety patient at the hospital must be applied in every hospital for quality improvement, especially for increasing patient safety culture. Keywords: Patient Safety Culture Hospital, Patient Safety, HSOPSC Asia